2014
DOI: 10.2298/jas1403243c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous plant extracts and inorganic fertilizer on the germination, growth and development of maize (Zea mays L.)

Abstract: Screen house experiments were carried out to examine the effects of aqueous leaf extracts of Tithonia diversifolia (Ti) and Vernonia amygdalina (Ve), as well as NPK fertilizer (15-15-15) on the germination, growth and development of maize. Fresh leaves were collected, washed with tap water, chopped and pounded, soaked in distilled water and filtered. The two filtrates were used to prepare extracts at 50 and 100% w/v. Four maize seeds were placed in Petri dishes laid out in a completely randomized design with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Both monocotyledon (maize) and dicotyledon (groundnut, cowpea and melon) response to initiation by imbibition for germination to progress to phase II. The radicle length of the cash crops were high when compared with the report of Chukwuka et al (2014), that reported a reduction in the radicle length of maize treated with aqueous extract of T. diversifolia and V. amygdalina respectively. The osmotic potentials of the different water sources affected the seeds in different ways.…”
Section: Resultsmentioning
confidence: 53%
“…Both monocotyledon (maize) and dicotyledon (groundnut, cowpea and melon) response to initiation by imbibition for germination to progress to phase II. The radicle length of the cash crops were high when compared with the report of Chukwuka et al (2014), that reported a reduction in the radicle length of maize treated with aqueous extract of T. diversifolia and V. amygdalina respectively. The osmotic potentials of the different water sources affected the seeds in different ways.…”
Section: Resultsmentioning
confidence: 53%
“…PN, NL and FA might have altered well-defined sequence of complex processes underlying a set of biochemical, physiological and morphological changes in millet and sesame (Bewley and Black, 1994;Bewley et al, 2013). The botanical extracts responded differently to seed germination (Chukwuka et al, 2014). Specifically, NL exhibited a laudable effect on sorghum and millet in comparison to sesame that was completely inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…The seeds were rinsed in four changes of sterile distilled water after which fifty uniform bean seeds were soaked overnight in 200 ml of each of the legume extracts then sown in moist chamber lined with sterile absorbent paper towel. In each moist chamber, 20 ml of each aqueous extract was used to wet the seeds while sterile distilled water was used for the control [12]. The treatments were replicated four times in a completely randomized design and repeated thrice.…”
Section: Determination Of the Effect Of Legume Extracts On Bean Seed mentioning
confidence: 99%
“…Production of phytotoxic substances depends on residue maturity, water content, pH and length of decomposition [10]. Aqueous extracts of crop residues contain toxic substances that can greatly delay germination and reduce shoot and root length of crops [11][12][13]. However, the chemical contents of the residues differ based on the nature of the solvents used in the extraction process as higher quantities of phenolics have been consistently isolated in alcohol extracts [14].…”
Section: Introductionmentioning
confidence: 99%